The Song-Ming Connection in the Ming Study of Ancient Inscriptions. (March 2015) - Sena, Yun-Chiahn C.
Abstract : This paper examines several Ming studies of ancient inscriptions by antiquarians such as Du Mu, Wen Zhengming, Zhao Han, Zhao Jun, and Yu Yizheng, with the attempt to re-evaluate the development of the so-called jinshi xue (Chinese antiquarianism specifically involving ritual bronzes and stone stelae) during this period. Ming jinshi study was traditionally considered to be in decline in the overall development of Chinese antiquarianism, due to the lack of innovative studies comparable to those made in the Song period. From the conceptual and materialistic perspectives, and in the context of how the Song legacy was perceived in the Ming period, this paper analyzes examples of the Ming jinshi writings, including prefaces, research entries, and colophons. The analyses demonstrate a strong interest among Ming antiquarians to forge an ideological continuity between the Song and Ming jinshi study; they also point to a set of connoisseurial practices in the functionality of rubbings, a major type of research materials for Chinese antiquarianism. In conclusion, in the light of the Song-Ming ideological continuity and the connoisseurial practices, the Ming jinshi study should be seen as a new phase in Chinese antiquarianism when ideological and materialistic aspects of the Chinese jinshi tradition were integrated into the core of Chinese elite culture.